Essential concepts of environmental communication an A-Z guide - Brereton, Pat (London New York Routledge, Taylor & Francis Group, 2022)
This book draws on a broad spectrum of environmental communications and related cross-disciplinary literature to help students and scholars grasp the interconnecting key concepts within this ever-expanding field of study. Aligning climate change and environmental learning through media and communications, particularly taking into account the post-COVID challenge of sustainability, remains one of the most important concerns within environmental communications. Addressing this challenge, Essential Concepts for Environmental Communication synthesizes summary writings from a broad range of environmental theorists, while teasing out provocative concepts and key ideas that frame this evolving, multi-disciplinary field. Each entry maps out an important concept or environmental idea and illustrates how it relates more broadly across the growing field of environmental communication debates. Including a full section dedicated to exploring what environmental communication might look like in a post-Covid setting, this volume: Offers cutting-edge analysis of the current state of environmental communications. Presents an up-to-date exploration of environmental and sustainable development models at a local and global level. Provides an in-depth exploration of key concepts across the ever-expanding environmental communications field. Examines the interaction between environmental and media communications at all levels. Provides a critical review of contemporary environmental communications literature and scholarship. With key bibliographical references and further reading included alongside the entries, this innovative and accessible volume will be of great interest to students, scholars and practitioners alike"--
Includes bibliographical references.
Keywords: Communication in the environmental sciences